Megakaryocyte Diversity in Ontogeny, Functions and Cell-Cell Interactions - Khatib-Massalha, Eman; Méndez-Ferrer, Simón (Frontiers in Oncology, 2022)
Hematopoietic stem cells (HSCs) rely on local interactions in the bone marrow (BM) microenvironment with stromal cells and other hematopoietic cells that facilitate their survival and proliferation, and also regulate their functions. HSCs and multipotent progenitor cells differentiate into lineage-specific progenitors that generate all blood and immune cells. Megakaryocytes (Mks) are hematopoietic cells responsible for producing blood platelets, which are essential for normal hemostasis and blood coagulation. Although the most prominent function of Mks is platelet production (thrombopoiesis), other increasingly recognized functions include HSC maintenance and host immune response. However, whether and how these diverse programs are executed by different Mk subpopulations remains poorly understood. This Perspective summarizes our current understanding of diversity in ontogeny, functions and cell-cell interactions. Cumulative evidence suggests that BM microenvironment dysfunction, partly caused by mutated Mks, can induce or alter the progression of a variety of hematologic malignancies, including myeloproliferative neoplasms (MPNs) and other disorders associated with tissue scarring (fibrosis). Therefore, as an example of the heterogeneous functions of Mks in malignant hematopoiesis, we will discuss the role of Mks in the onset and progression of BM fibrosis. In this regard, abnormal interactions between of Mks and other immune cells might directly contribute to fibrotic diseases. Overall, further understanding of megakaryopoiesis and how Mks interact with HSCs and immune cells has potential clinical implications for stem cell transplantation and other therapies for hematologic malignancies, as well as for treatments to stimulate platelet production and prevent thrombocytopenia.